Pengaruh Fanatisme, Kualitas Produk, dan Perilaku Konsumtif Terhadap Keputusan Pembelian Jersey Di Graha Persib Bandung - Irsyad, Muhamad Agung; Suarna, Indri Ferdiani (PT Maju Malaqbi Makkarana, 2024)
The rapid pace of business development makes this activity very interesting for the public. This phenomenon is clearly visible throughout society, along with the emergence of many companies in response to various demands, needs, and desires. Given the rapid progress of the business world, it is very important for every company to consistently produce ideas and progress in their offerings, with the aim of motivating individuals to make purchases. The type of research used is descriptive and verification with an approach using quantitative methods, with data distribution techniques using questionnaires. The results of multiple linear regression analysis show that partially Fanaticism has an effect of 3.497, Product Quality is 4.261, and Consumptive Behavior 6.507 has a positive and significant influence on Purchasing Decisions. Simultaneously Fanaticism, Product Quality and Consumptive Behavior have a positive and significant influence on Purchasing Decisions of 46.033 Then it has a coefficient of determination of 26%.